Wife as Sole Breadwinner in Islamic Law Perspective - Putra, Andi Wardana Putra Wardana; Soediro, Soediro (UMPurwokerto Law Review, 2021)
The obligation to provide a living is an obligation for a husband, but in reality, now the husband's obligation is also carried out by a wife when the husband cannot provide for the family's needs. In married life, it should be, and a husband should be responsible to his family. The husband also has a very dominant role in the welfare and survival of together. What factors cause the wife to be the sole breadwinner and the Islamic Law's View of the wife as the sole breadwinner. This type of research is normative juridical. The normative juridical method is carried out through literature studies that examine mainly secondary data in laws and regulations, agreements or contracts, other legal documents, research results, assessment results, and other references. A literature study is carried out by studying the literature related to the problem under study. Data collection is carried out by library research (library research) to obtain data in documents and writings by searching for statutory regulations, documents, scientific literature, and research by experts. The results showed that several factors cause the wife to be the sole breadwinner, namely economic factors, the influence of the times, lifestyle, self-existence, educational factors, and husbands who are not responsible for making a living. Islamic law does not prohibit wives from earning a living as long as they do not leave Islamic law, even allowing their husbands to make a living for the family, as long as they do not neglect their responsibilities as housewive Keywords: Wife, Sole Breadwinner, Family, Islamic Law